National Health Policy and factors predicting its implementation at the local level in Nepal: an exploratory cross-sectional study - Khadka, Dipendra; Xinyi, Zhang; Mengjie, Zhang; Bhusal, Rajan; Zhang, Chichen (Frontiers in Public Health, 2025)
IntroductionNepal’s National Health Policy (NHP), periodically revised since 1991, aims to enhance citizens’ health and well-being within the federal democratic framework established in line with the Constitution of Nepal 2015. This study evaluated the implementation status, challenges, and opportunities of the NHP at the local level in Nepal.Materials and methodsA descriptive cross-sectional study was conducted in the Lumbini province among 166 health workers selected through simple random sampling. Data were collected from October 10 to November 15, 2024, using a structured questionnaire developed in Nepali through literature review and expert consultations. Field researchers administered the questionnaire. The final tool assessed awareness, challenges, and factors influencing the National Health Policy implementation. Descriptive statistics and inferential statistics using binary logistic regression were used for analysis.ResultsThe study revealed moderate awareness of NHP among health workers, with 60.2% somewhat familiar with the policy. Major implementation challenges included inadequate infrastructure (62.0%), limited access to skilled healthcare professionals (56.0%), and insufficient financial resources (54.2%). Regular use of technology significantly increased the likelihood of positive NHP implementation outcomes (OR: 5.448, 95% CI: 1.988–14.926, p = 0.001). Age (OR: 0.919, 95% CI: 0.880–0.961, p < 0.001) and years of experience (OR: 0.934, 95% CI: 0.895–0.975, p = 0.002) were significantly associated with attitudes toward NHP implementation. While 65.7% of respondents were somewhat aware of local NHP initiatives, 86.8% expressed the need for additional training and resources.ConclusionThe study found moderate awareness of the National Health Policy among health workers, with key challenges including inadequate infrastructure, limited skilled professionals, and insufficient funding. Regular use of technology significantly improved implementation outcomes, while younger age and less experience were linked to more positive attitudes. Despite some awareness of local initiatives, most participants stressed the need for additional training and resources to enhance policy execution.